Gênero discursivo carta do leitor: uma prática de escrita no ensino de língua portuguesa - JURACI SOARES DA SILVA (2024)
SILVA, Juraci Soares. Discursive genre reader's letter: a writing practice in Portuguese language teaching. Três Lagoas: Três Lagoas Campus, Federal University of Mato Grosso do Sul, 2024. 138 f. (Masters dissertation). The general objective of this work is to contribute to improving the reader's writing proficiency via the letter genre, investing in strategies that encourage the student's authorial process. Our specific objectives are to enable the development of writing through teaching the reader's letter discursive genre; enable interaction in the social environment of students' writing, in a way that helps the student feel like a writer/author and analyze the effects of meaning present in the students' written production. For greater visibility of student protagonism, these writings were posted on the blog created for this purpose. The theoretical support for the development that we propose is located in a dialogical perspective, based on the works of Bakhtin (2011, 2014); Brait (2005) and Fiorin (2020). Regarding writing, we are based on Antunes (2003, 2014), who postulates writing as a means of social interaction. In the discursive aspect, we anchored in the theories of Coracini (1999, 2001, 2010); Foucault (2014, 2020); Geraldi (2013) and Orlandi (2012, 2013). To create the corpus of analysis for this research, students were given the opportunity to read, interpret and write in various situations, including the production of the discursive genre from the personal letter to the reader's letter. Based on the theoretical assumption that significant textual production is one in which the student has what to say, a reason to say it and who to say it to (Geraldi, 2013), materialized in discursive genres, in various activities in the human sphere, we formulate the hypothesis that that providing students with free themed reading opportunities, related to their social and personal practices, can contribute to improving their writing skills in the reader's letter genre. For the development of this research, it is necessary to unfold this hypothesis into the following research questions: How can reading and writing practice, through the reader's letter genre, contribute to the process of developing skills and competencies? related to the experience of these students’ words? Does the practice of didactic-pedagogical activities promote the creation of authorship in the student’s written production? This dissertation is divided into three chapters. In the first, we explained the theoretical concepts of dialogism, understood as a form of interaction through reading and writing in different discursive genres, considering them as fundamental elements in teaching the Portuguese language. The second chapter deals with theoretical-methodological procedures, which are based on qualitative and interpretive action research, the research location and the stages of development of the intervention project. The third chapter focuses on the results of the analysis of the most relevant and representative textual productions of the research participants, with emphasis on the first and last versions of the texts. The results found that writing the reader's letter genre with a theme of free choice is capable of contributing to and improving students' writing competence with autonomy and criticality, as well as the practice of didactic-pedagogical activities with genres, corrections and individual and collaborative rewriting demonstrated significant advances in the constitution of student authorship. Keywords: Reading; written production; reader's letter; collaborative correction.